2013
DOI: 10.1186/1742-4755-10-s1-s2
|View full text |Cite
|
Sign up to set email alerts
|

Born Too Soon: The global epidemiology of 15 million preterm births

Abstract: This second paper in the Born Too Soon supplement presents a review of the epidemiology of preterm birth, and its burden globally, including priorities for action to improve the data. Worldwide an estimated 11.1% of all livebirths in 2010 were born preterm (14.9 million babies born before 37 weeks of gestation), with preterm birth rates increasing in most countries with reliable trend data. Direct complications of preterm birth account for one million deaths each year, and preterm birth is a risk factor in ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
1,513
11
103

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,765 publications
(1,659 citation statements)
references
References 74 publications
32
1,513
11
103
Order By: Relevance
“…The finding of higher odds of ventilation of LBW infants supports the previous finding of a reduced rate of intrapartum stillbirths after training in HBB, as almost half of those stillbirths were LBW infants [8]. The data for gestational age in this study were not complete, but the cases with available information on gestational age confirmed the global estimates of the relatively high proportion of moderately premature infants [25,26]. This study focused on evaluating differences in steps of neonatal resuscitation between LBW and NBW infants; therefore it is difficult to compare with previous observational studies of HBB interventions.…”
Section: Discussionsupporting
confidence: 86%
“…The finding of higher odds of ventilation of LBW infants supports the previous finding of a reduced rate of intrapartum stillbirths after training in HBB, as almost half of those stillbirths were LBW infants [8]. The data for gestational age in this study were not complete, but the cases with available information on gestational age confirmed the global estimates of the relatively high proportion of moderately premature infants [25,26]. This study focused on evaluating differences in steps of neonatal resuscitation between LBW and NBW infants; therefore it is difficult to compare with previous observational studies of HBB interventions.…”
Section: Discussionsupporting
confidence: 86%
“…Normal pregnancy represents a unique, transient, and dynamic state of altered anatomy, physiology, and immune function. Preterm birth, i.e., before 37 wk of gestation, occurs in 11% of pregnancies and is the leading cause of neonatal death (4). In both term and preterm pregnancies, the interplay between the microbiota and the host remains poorly understood.…”
mentioning
confidence: 99%
“…Evidence shows that impaired inflammatory response is implicated in numerous female reproductive tract pathologies including menstrual disorders (Sales & Jabbour 2003), endometriosis-associated infertility (Gupta et al 2008), recurrent miscarriage (von Wolff et al 2000, Laird et al 2003, intrauterine growth restriction (Heyborne et al 1994), preeclampsia , Rinehart et al 1999) and preterm labor (Romero et al 2006. Infertility has an estimated global prevalence of 9% with >72 million infertile women worldwide (Boivin et al 2007), whereas preterm birth and preeclampsia, the two leading causes of perinatal mortality and morbidity, have an estimated prevalence of >11% (Blencowe et al 2013) and 3-5% (Ananth et al 2013 respectively. Therefore, understanding the mechanisms by which inflammation is untimely triggered in the uterus is fundamental to developing effective therapeutics to improve fertility and decrease poor obstetrical outcomes.…”
Section: Introductionmentioning
confidence: 99%